Microplastic Pollution in Indonesian Waters: Characteristics, Ecological Impacts, and Mitigation Strategies - Fathun Rahman; Fitri Afifah Nasution; Nadya Nadya; Firdus Firdus; Alia Rizki; Muhammad Nasir (Jurnal Biologi Tropis, 2026)
Microplastic pollution in waters poses a serious threat to aquatic ecosystems in Indonesia. This study aims to examine the variations in microplastic types based on shape and polymer, abundance, impacts on aquatic biota, and solutions through literature reviews from various sources. The results indicate that microplastic pollution has spread widely from western to eastern Indonesia. The highest abundance was found in areas with high population density and anthropogenic activity, such as Banten Bay, Jakarta Bay, and the South Coast of Java. Microplastic forms are dominated by fragments, fibers, films, and foams. Polymer identification shows a dominance of PP and PE as well as specific industrial polymers. The impact of contamination occurs on various biota, from fish to invertebrates, causing decreased nutritional quality, digestive damage, and metabolic disorders. Mitigation includes reducing single-use plastics, improving waste management, Wastewater Treatment Plant (WWTP) technology, bioremediation, as well as the role of the community and government policies.